2021
DOI: 10.1186/s12909-021-02550-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring graduate occupational and physical therapy students’ approaches to studying, self-efficacy, and positive mental health

Abstract: Background Occupational and physical therapy academic programs are rigorous. Increased rates of student anxiety and depression may impact learning. Data on student study skills, self-efficacy, and mental health is limited. This study explored relationships between students’ self-efficacy, mental health factors, and approaches to studying. Method A cross-sectional study was designed. Seventy-three students completed the Approaches and Study Skills I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
2
10
2
1
Order By: Relevance
“…The study showed that higher self-efficacy was related to higher deep approach ratings, while higher mental health ratings were related to higher strategic approach ratings and lower surface approach ratings. The results in this study compared to the previous one (DaLomba et al, 2021) support the notion that general self-efficacy and positive mental health show relatively consistent associations over time with student approaches to studying.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The study showed that higher self-efficacy was related to higher deep approach ratings, while higher mental health ratings were related to higher strategic approach ratings and lower surface approach ratings. The results in this study compared to the previous one (DaLomba et al, 2021) support the notion that general self-efficacy and positive mental health show relatively consistent associations over time with student approaches to studying.…”
Section: Discussionsupporting
confidence: 84%
“…This may suggest reciprocity in the relationship between students' perceived self-efficacy and approaches to learning in that they might influence each other in selfstrengthening cycles that may potentially be enhanced by instructorfacilitated deep approaches. While the first study showed that self-efficacy was positively related to the deep and strategic approaches and negatively related to the surface approach (DaLomba et al, 2021), this study only revealed a significant and positive relationship between the students' selfefficacy and their deep approach ratings. However, all associations were in the same direction as in the previous study, lending support to the notion that associations between self-efficacy and learning approaches are relatively stable over time.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Therefore, higher dropout rates among students with higher scores on surface learning might have been expected if the addition of three surveys compounded these feelings. Strategic approach behaviors have been associated with desirable states and outcomes, such as higher self-efficacy [ 5 ] and better academic results [ 34 ], while surface approach behaviors have been linked with poorer self-efficacy and poorer mental health [ 5 ], as well as poorer academic outcomes [ 35 ]. Thus, the results indicate that consistent study participation may be somewhat more commonplace among higher functioning, academically oriented students with productive study approaches.…”
Section: Discussionmentioning
confidence: 99%
“…With further exploration, a third strategic approach that addresses student organization and self-regulation around work was added [ 4 ]. Recent evidence from occupational therapy student studies showed that students who adopt deep and strategic approaches tend to have higher reported self-efficacy and positive mental health [ 5 ] and are more inclined to adopt a positive outlook on the broader learning outcomes of the study program. However, whether these students are more inclined to participate in educational research is not known.…”
Section: Introductionmentioning
confidence: 99%